Analysis methods for assessing survivability information-measuring complex aeronautical equipment regional aircraft - Бажан, В.І.; Казак, В.М. (Proceedings of National Aviation University, 2007)
The analysis methods estimation vitality informatively-measuring complex pilotage-navigation equipment of regional airplane is considered.